2020
DOI: 10.1186/s12870-019-2170-7
|View full text |Cite
|
Sign up to set email alerts
|

The pathogen Moniliophthora perniciosa promotes differential proteomic modulation of cacao genotypes with contrasting resistance to witches´ broom disease

Abstract: BackgroundWitches’ broom disease (WBD) of cacao (Theobroma cacao L.), caused by Moniliophthora perniciosa, is the most important limiting factor for the cacao production in Brazil. Hence, the development of cacao genotypes with durable resistance is the key challenge for control the disease. Proteomic methods are often used to study the interactions between hosts and pathogens, therefore helping classical plant breeding projects on the development of resistant genotypes. The present study compared the proteomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
171
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(185 citation statements)
references
References 80 publications
10
171
1
Order By: Relevance
“…In addition, greater MGDG (18:2/16:0) abundance was found in Fujian wheat samples while compared with that from Gansu, which might due to the rainfall differences between two provinces according to the previous study that changes of wheat lipid constitutions happened under water shortage treatment [ 56 ]. Further, the observed increasing ratio of DGDG and MGDG might be due to the cylindrical shape of DGDG with two galactosyls, which contributed to the formation of a stable bilayer phase while MGDG tended to form an unstable hexagonal phase [ 10 ].…”
Section: Resultsmentioning
confidence: 97%
“…In addition, greater MGDG (18:2/16:0) abundance was found in Fujian wheat samples while compared with that from Gansu, which might due to the rainfall differences between two provinces according to the previous study that changes of wheat lipid constitutions happened under water shortage treatment [ 56 ]. Further, the observed increasing ratio of DGDG and MGDG might be due to the cylindrical shape of DGDG with two galactosyls, which contributed to the formation of a stable bilayer phase while MGDG tended to form an unstable hexagonal phase [ 10 ].…”
Section: Resultsmentioning
confidence: 97%
“…Strigolactones are hormones that inhibit tillering and shoot branching through the MAX-dependent pathway [ 82 ] and have been widely implicated in acclimation to environmental stresses [ 83 , 84 ]. Recent studies suggest that CRISPR/Cas9-mediated mutagenesis of CCD8 alters the root and shoot architecture and provides resistance against some parasitic weeds [ 85 , 86 , 87 ]. In our study, CCD8B protein was induced by CPPU during severe drought stress (day 14) at both the tillering and grain-filling stages.…”
Section: Resultsmentioning
confidence: 99%
“…However, several reports have demonstrated that large-scale genomic analysis may provide more accurate results than pedigree analysis 27 , 28 . This kind of genome-based pedigree analysis has already been performed in apple 51 . The recent publication of two almond reference genomes 4 , 52 and the increasing availability of quality genomic data opens opportunities to complement our study and obtain more complete and accurate pedigrees based on genomic variability.…”
Section: Discussionmentioning
confidence: 99%